A statistical process control study on Century Pipes Corporation (a research study) - Ayes, Sheryl (College of Engineering, 2000)
Today, quality is one of the major requirements in every production or manufacturing firm. It is one objective that every company should meet to ensure customer satisfaction. As partial fulfillment of the requirements in the course Industrial Engineering 135, Industrial Quality Control, this document presents the study conducted by the research group. The study is about is Industrial Quality Control. It dealt with process control charts, specifications and tolerances, acceptance sampling, reliability and life testing. In the conduct of the study, the different practices in an actual industrial setting were considered with the aim of supplementing the theoretical knowledge learned during the class lectures. It also aims to apply the Statistical Quality Control tools and techniques in an actual setting. In line with this, the research group approached Century Pipes Corporation. Information about the company was documented and its Company Profile presented. Sampling plans and quality techniques used in the company were also included in the paper. CPC manufactures orange brown sanitary pipes and commercial grade pipes. The company employs single sampling acceptance plan wherein in every hour of their production, two randomly selected pipes are inspected for defects. If these two pipes meet the specifications and tolerance limits, the whole batch is accepted. If not, the whole hour production is rejected. However the company has to make sure that these two pipes are representative of the whole batch. In the course of the study, the group was able to identify three major problems, namely : non-uniform wall thickness around circumference and along the pipe's length, deficiency in outer and inner diameter, and low impact strength. These problems were identified using Failure Mode Effects and Criticality Analysis. These were the problems that exhibited high Risk Priority Number (RPN). These were then verified using Ishikawa Diagram and Pareto Chart. Actual data from the company, such as measurements of wall thickness, inner and outer diameter and ovality were studied. Afterwards, control charts were constructed for each critical quality characteristic. These control charts were then analyzed and revised. For further analysis, Cpr and Cpk of the process were also computed. Histograms were used to estimate process capability. The analysis of the process capability showed that the company is performing outside its specifications. After the problems were presented and analyzed, the group made recommendations that the company could implement to improve their present performance. Areas for further study were also provided to offer the company of the fields that they should also consider giving appropriate attention. These were the areas that the research group failed to cover because of the unavailability of data and information. These were the data and information that the company could not provide the research group.